Safety and Efficacy of Alendronate to Treat Osteopenia in Children During Therapy for Acute Lymphoblastic Leukemia: A Retrospective Cohort Study of Sequential Outcomes. Issue 4 (13th May 2023) - MacDonald, Paula; Cranston, Amy; Virdee, Misha; Farncombe, Troy; Athale, Uma; Barr, Ronald D.
Abstract : Background: Low bone mineral density is encountered in children with acute lymphoblastic leukemia (ALL) before, during, and after treatment. Prior experience with alendronate, an oral bisphosphonate, demonstrated high tolerability and evident clinical efficacy. However, concerns have been expressed about the long-term safety and utility of such agents in children. Procedure: Sixty-nine children with ALL received alendronate for a mean of 87 weeks after dual-energy radiograph absorptiometry. Dual-energy radiograph absorptiometry was repeated following the completion of alendronate, and 5 to 9 years later in a subgroup of 32 children. Lumbar spine areal bone mineral density (LS aBMD) Z scores were obtained. Results: The mean LS aBMD Z score rose from −1.78 to−0.47 ( P <0.0001). There was a modest median loss of LS aBMD subsequently in the 32 subjects on long-term follow-up. Almost 80% (N=172) of the children remain in continuous complete remission at a mean of 14.5 years from diagnosis. Of those who received alendronate, which was almost uniformly well tolerated, 7/69 (10.3%) relapsed compared with 19/89 (21.3%) who did not receive the drug. Discussion: Alendronate appears to be well tolerated and moderately effective in osteopenic children with ALL. Whether it offers protection against relapse of leukemia needs further study.